Preoperative sequential short-course radiation therapy and FOLFOX chemotherapy versus long-course chemoradiotherapy for locally advanced rectal cancer: a multicenter, randomized controlled trial (SOLAR trial) - Min Kyu Kang; Soo Yeun Park; Jun Seok Park; Hye Jin Kim; Jong Gwang Kim; Byung Woog Kang; Jin Ho Baek; Seung Hyun Cho; An Na Seo; Duck-Woo Kim; Jin Kim; Se Jin Baek; et al. (BMC Cancer, 2023)
Abstract Background Preoperative (chemo)radiotherapy has been widely used as an effective treatment for locally advanced rectal cancer (LARC), leading to a significant reduction in pelvic recurrence rates. Because early administration of intensive chemotherapy for LARC has more advantages than adjuvant chemotherapy, total neoadjuvant therapy (TNT) has been introduced and evaluated to determine whether it can improve tumor response or treatment outcomes. This study aims to investigate whether short-course radiotherapy (SCRT) followed by intensive chemotherapy improves oncologic outcomes compared with traditional preoperative long-course chemoradiotherapy (CRT). Methods A multicenter randomized phase II trial involving 364 patients with LARC (cT3–4, cN+, or presence of extramural vascular invasion) will be conducted. Patients will be randomly assigned to the experimental or control arm at a ratio of 1:1. Participants in the experimental arm will receive SCRT (25 Gy in 5 fractions, daily) followed by four cycles of FOLFOX (oxaliplatin, 5-fluorouracil, and folinic acid) as a neoadjuvant treatment, and those in the control arm will receive conventional radiotherapy (45–50.4 Gy in 25–28 fractions, 5 times a week) concurrently with capecitabine or 5-fluorouracil. As a mandatory surgical procedure, total mesorectal excision will be performed 2–5 weeks from the last cycle of chemotherapy in the experimental arm and 6–8 weeks after the last day of radiotherapy in the control arm. The primary endpoint is 3-year disease-free survival, and the secondary endpoints are tumor response, overall survival, toxicities, quality of life, and cost-effectiveness. Discussion This is the first Korean randomized controlled study comparing SCRT-based TNT with traditional preoperative LC-CRT for LARC. The involvement of experienced colorectal surgeons ensures high-quality surgical resection. SCRT followed by FOLFOX chemotherapy is expected to improve disease-free survival compared with CRT, with potential advantages in tumor response, quality of life, and cost-effectiveness. Trial registration This trial is registered at Clinical Research Information under the identifier Service KCT0004874 on April 02, 2020, and at Clinicaltrial.gov under the identifier NCT05673772 on January 06, 2023.